PENERAPAN PSAK NO. 50 (REVISI 2006) DAN PSAK NO.55 (REVISI 2006) PADA PT. BANK RIAU KEPRI CABANG PEMBANTU UJUNG BATU - Yuliza, Arma (E-Journal Cano Ekonomos, 2013)
PSAK No. 50 (Reviseing 2006) arranging about monetary instrument expression and presentation. PSAK No. 55 (Reviseing 2006) arranging about confession and measurement of monetary instrument. Matter which enough krusial from both the PSAK to bank is that credit as bank asset classified at "And Receivables Loan" which its of him is by cost amortized, this matter bring consequence that credit value (in this case bank asset) will influence by projection of cashflow of asset. This research aim to to know how applying of PSAK No. 50 (Reviseing 2006) and PSAK No. 55 (Reviseing 2006) at PT. Bank of Riaukepri Ministrant Branch Tip of Stone which is have location to in Road;Street General of Sudirman District Of Back Part Stone Sub-Province of Rokan Pate;Upstream by using descriptive method. From result of research known that PT. Bank of Riau Ministrant Kepri Branch of Ujungbatu have applied PSAK No. 50 (Reviseing 2006) and PSAK No. 55 (Reviseing 2006) effectively dated 1 January 2012 pursuant to released by Indonesia Bank.